2008
DOI: 10.1016/j.mcn.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of astrocytes and chemokine systems in acute TNFα induced demyelinating syndrome: CCR2-dependent signals promote astrocyte activation and survival via NF-κB and Akt

Abstract: Chemotactic factors known as chemokines play an important role in the pathogenesis of Multiple Sclerosis (MS). Transgenic expression of TNFα in the central nervous system (CNS) leads to the development of a demyelinating phenotype (TNFα-induced demyelination; TID) that is highly reminiscent of MS. Little is known about the role of chemokines in TID but insights derived from studying this model might extend our current understanding of MS pathogenesis and complement data derived from the classic autoimmune ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…The target of CCL2, involved in mediating the neuroprotective activity of the chemokine, has not been addressed in the present study: previous reports showed that the main receptor for CCL2 is CCR2, but this chemokine can also bind to other receptors like CCR1, CCR4, and L-CCR, albeit with lower affinity Savarin-Vuaillat et al, 2007;White et al, 2007;Quinones et al, 2008). In addition, CCR2 expression in brain parenchyma is controversial.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The target of CCL2, involved in mediating the neuroprotective activity of the chemokine, has not been addressed in the present study: previous reports showed that the main receptor for CCL2 is CCR2, but this chemokine can also bind to other receptors like CCR1, CCR4, and L-CCR, albeit with lower affinity Savarin-Vuaillat et al, 2007;White et al, 2007;Quinones et al, 2008). In addition, CCR2 expression in brain parenchyma is controversial.…”
Section: Discussionmentioning
confidence: 86%
“…However, recent analyses of CNS tissues of CCR2-RFP mice provided no evidence of CCR2 expression either on neurons, astrocytes, microglia, or oligodendrocytes (Saederup et al, 2010), apparently limiting CCR2 expression in the brain to pathological conditions with infiltration of Ly6C(hi) monocytes. This last piece of evidence suggests that, at least under physiological conditions, other receptors might be involved in transducing CCL2-mediated signaling in the brain, as observed in astrocytes (Quinones et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment of astrocytes with LPS [68] or TNF-α [69] caused increased expression of various chemokines including MCP-1, MIP-1α, RANTES, KC, MIP-2. In an experimental model of multiple sclerosis, astrocytes were found to be the predominant source of MCP-1, MIP-1α and RANTES [70]. It is believed that chemokines secreted by astrocytes at the neurovascular unit in brain may facilitate and recruit the entry of blood cells that home to the injured regions [71].…”
Section: Discussionmentioning
confidence: 99%
“…RNase protection assay (RPA) was performed as described previously (23, 29). Total RNA was isolated from homogenized ear explants and used to perform the RPA using RiboQuant Multiprobe RNase Protection Assay Kit (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%